Medroxyprogesterone acetate plus estradiol cypionate: evaluation at the National Hospital Cayetano Heredia. - Trelles, Juan (2015)
OBJECTIVES: Introductory study of contraceptive monthly deposit, 25 mg of medroxyprogesterone acetate (AM) plus 5 mg estradiol cypionate (EC), the National Hospital Cayetano Heredia, to assess their effectiveness, continuity and reasons for discontinuation. DESIGN: Prospective, longitudinal descriptive of 159 women who would come to the family planning clinic and after counseling voluntarily chose AM + CE for contraception. They were given one injection every 30 days and were followed up for two years, evaluating the efficacy and side effects. For data analysis a life table was used. RESULTS: No pregnancies were observed. The most common side effects were irregular pattern of monthly bleeding, amenorrhea, headache and nausea. The rate of continuing the second year was 43.3 and causes of discontinuation included bleeding, amenorrhea, medical reasons and the desire of pregnancy. CONCLUSIONS: AM + CE is a hormonal contraceptive effective reservoir and well accepted by users.